Pendidikan Islam dan Adab Belajar Perspektif KH. Hasyim Asy’ari - Abdillah, Sultan (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2023)
This thesis aims to find out how Islamic education is from the perspective of KH. Hasyim Asy'ari, apart from that, this research also aims to find out how manners are in learning from KH's perspective. Hasyim Asy'ari. The type of research used in this research is qualitative library research. The approach used is a philosophical analysis approach to the thoughts of figures at certain times in the past, and the research methodology uses a historical approach. The data sources for this research are primary and secondary data sources, the primary data in this research are books written by KH. Hasyim Asy'ari, while the secondary data in this research are books, articles in magazines and online, theses, theses and journals. The data collection method in this research is the documentation method. The data analysis technique used in this research is the Spradley model data analysis technique, namely domain, textonomic, componential, and cultural theme analysis. The results of this research can be concluded that this research shows the nature of Islamic education in the view of KH. Hasyim Asy'ari's aim is to maintain the title of the noblest creature placed on humans and education lies in its contribution to creating a cultured and ethical society. Then Adab studied KH's perspective. Hasyim Asy'ari which has been explained in one of his books, Adabul Alim Wal Muta'allim, which includes the primacy of knowledge and scholars as well as the privileges of learning and teaching, the personal etiquette of a student, the etiquette of a student towards a teacher, the etiquette of a student in learning, the personal etiquette of a teacher, a teacher's etiquette in teaching, a teacher's etiquette when meeting his students, and a person's etiquette towards textbooks.